Pneumoscrotum after Colonoscopy - Sandeep Singh; Manika Thakur (Canadian Journal of Gastroenterology)
Pneumoscrotum is an unusual problem that is very rarely associated with gastrointestinal endoscopy procedures. It has been reported to occur after colonoscopy and polypectomy. The present paper describes the case of an 81-year-old man with benign pneumoscrotum that formed after polypectomy at the site of a previous rectal polyp. The pneumoscrotum was managed with conservative treatment.